Reconstruction of Money Politics Handling Mechanisms for the Realization of Fair and Dignified Elections (Law Research Review Quarterly, 2018)
Elections are the mandate of the constitution that must be carried out by the government, in this case ensuring and protecting the exercise of people's sovereignty in channeling their political rights in elections. Money politics is carried out because there is no commitment from officials or part of the community in holding moral values, the desire to get an office instantly, and one way to maintain power. Therefore, it must be instilled in the values ​​of faith, giving strict punishment to the person who bribes, the transparency of both the central government and below. Money politics is very much against the principles of democracy and the principles of humanity that are fair and civilized (the values ​​contained in the 2nd precepts), leaders must get legitimacy from the people who choose them with democratic principles. Elections with integrity (electoral integrity) must be realized and supported by all parties, including the creation of good governance. From elections with integrity, a fair and dignified election process can be realized. The election is the will of the Indonesian nation to establish itself as a democratic state, therefore elections must be carried out by providing certainty and guarantee, honest, fair, free, and confidential. The toughest challenge faced by democratic countries is overcoming the practice of money politics. This money politics harms democracy and will bury the noble ideals of democracy. Related to the impact of violations on elections, including money politics. The form of this provision must be drafted by law.